Fatty acids profile and anti-nutritional factors of raw and roasted Caryocar brasiliense almonds - Damiani, Clarissa (2013)
Caryocar brasiliense Camb. is one of the most abundant fruits in the Brazilian Savannah. Its pulp is highly appreciated in the regional cuisine, but its almond (also edible) is little used. The consumption of raw almond can cause digestive problems, due to the possible presence of anti-nutritional factors, as well as roasting can nutritionally change it. This study aimed at evaluating the centesimal composition, fatty acids profile and anti-nutritional factors, in raw and roasted (at 270ºC, for 15 minutes) Caryocar brasiliense almonds from the Goiás State, Brazil, submitted to analyses of centesimal composition (moisture, proteins, lipids, ashes, carbohydrates and energy value), fatty acids profile and anti-nutritional factors (trypsin, tannin and phytate inhibitors). The centesimal composition and anti-nutritional factors, respectively for raw and roasted almonds, showed the following values: moisture: 25.40% and 1.70%; ashes: 3.90% and 4.60%; proteins: 13.40% and 14.70%; lipids: 24.70% and 25.70%; carbohydrates: 32.50% and 53.30%; and energy value: 406.20 kcal/100 g and 503.00 kcal/100 g, with absence of trypsin inhibitors and tannins with 1.21% and 1.17% and phytates with 2.64% and 1.86%. In the fatty acids profile, respectively for raw and roasted almonds, 86.90% and 84.61% of saturated acids and 10.57% and 10.40% of unsaturated acids were observed. The roasting of almonds did not significantly affect (p > 0.05) only the protein, thus interfering both in the nutritional and anti-nutritional characteristics.